Libyan teachers selection of materials in EFL reading classroom - Aljadi, Abdulhadi Masaud Alsanousi (2018)
The aim of the study is to identify the materials used for teaching English as a ForeignLanguage (EFL) reading and the difficulties in selecting materials that cater to learners needsand abilities. It is also aimed to analyse teachers views on English Language Teaching(ELT) materials in reading lessons and the principles considered in selecting or constructingreading materials. Qualitative method was applied in this study. The data were collected throughpre-interview, reading lesson plans and post interview which involved three English as ForeignLanguage (EFL) Libyan teachers from Libyan international schools. The data was analysed usingthe semantic analysis. The finding showed that the common reading materials used by Englishas a Foreign Language (EFL) teachers are reading texts, quizzes, pictures, and musicvideos. It was proven that the factors that influence teachers views on readingmaterials selection are motivation, proficiency, interest, and subject matter. This study alsofound that teachers views on reading materials are highly influenced by their teachingexperience as well as students and contextual factors. However, the participants stressedthat the insufficient professional development training impedes them in gaining enough skills inteaching English as a Foreign Language (EFL) reading and in selecting materials. This studyprovides better understanding and justification of the criteria set by the respective teachers inselecting or constructing reading materials. It will help educators and education policy plannersthrough insights on the needs of English as Foreign Language (EFL) teachers in enhancing theirknowledge in materialsselection.